PENGARUH INTELLECTUAL CAPITAL, MARKET VALUE ADDED DAN DEBT TO EQUITY RATIO TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2022 - Safrudin Safrudin; Frisca L. Siagian Frisca L. Siagian; Bambang Santosa Bambang Santosa; Adam Adam (LPPM Swadaya Institute of Business and Communication, 2023)
This study aims to examine the effect of Intellectual Capital (IC), Market Value Added (MVA), and Debt to Equity Ratio (DER) on the financial performance (Return on Equity) of a manufacturing company listed in the Indonesia Stock Exchange (Bursa Efek Indonesia) in 2017- 2021” The study using purposive sampling method to collect samples. The population of this study amounted to 9 from 26 companies that are in accordance with predetermined criteria. Data tests are done by using the software SPSS 25 and using a descriptive test, classical assumption test, multiple linear regression test, and hypnotist test. The results of this study state that partial Intellectual Capital (IC) has a positive effect on financial performance; Market Value Added in partial (MVA) has a positive effect on financial performance and in partial Debt to Equity Ratio (DER) has no positive effect on financial performance. While simultaneously together Intellectual Capital (IC), Market Value Added (MVA), and Debt to Equity Ratio (DER) have a positive effect on the financial performance of manufacturing companies segmented in food and beverage listed in the Indonesian Stock Exchange period 2017-2021.